GRAMMATICAL METAPHOR REPRESENTATIONS AND TRANSGRAMMATICAL SEMANTIC DOMAINS IN THE SOCIAL CONTEXTS OF ENGLISH LANGUAGE LEARNING IN INDONESIA - Amrin Saragih (Universitas Islam Sumatera Utara (UISU), 2018)
Grammatical metaphor refers to the coding of meaning or experience in the manner as if the meaning or experience were coded by another lexicogrammatical coding. Metaphorical representation implies that there are two manners of coding, namely the congruent or literal and incongruent or metaphorical coding. Transgrammatical semantic domains extends meaning by a range of grammatical units. Transgrammatical semantic coding implies that agnated meanings are realized by more than one semantic unit. Grammtical metaphor representation inherently contains transgrammatical coding. This paper addresses grammatical metaphor commonly used in texts of science, technology and academics, which are very difficult for Indonesian students to understand and translate into good bahasa Indonesia (BI). By applying knowledge or competence of gramatical metaphor and transgrammatical semantic domain Indonesian students are expected to effectively learn the meaning of English text of science, technology and academics and to translate the texts into good BI.